Pengaruh Kualitas Pelayanan Terhadap Kepatuhan Wajib Pajak Dalam Membayar Pajak Kendaraan Bermotor (Studi Kasus Samsat Kota Medan) - Islami Rambe, Muhammad Irfan; Hutama Hutabarat, Dany Try; Reihansyah, Muhammad Naufal (MODELING: Jurnal Program Studi PGMI, 2023)
Regional Tax is a form of improvement in increasing Regional Original Income (PAD) as a source of funds to support development that needs to be continuously driven through cultivating new sources and improving the management of existing taxes. So regarding this matter, Regional Tax is a form of mandatory contribution to the region that is owed by an individual or entity that is coercive based on the Law, without receiving direct compensation and is used for Regional needs for the greatest prosperity of the people. The problem formulation discussed is how to implement an electronic system in motor vehicle tax payment services and what are the obstacles to implementing an electronic system in motor vehicle tax payment services. Taxpayers who pay motor vehicle tax at the Medan City UPPT SAMSAT Office must first fill out a Motor Vehicle Registration and Data Collection Letter (SPPKB) clearly, completely and correctly according to the identity of the motor vehicle and the taxpayer concerned and signed by the Taxpayer or his Proxy. . The SPPKB is submitted no later than 14 days from the time of ownership and/or control, for new motorized vehicles until the end date of the tax period for old motorized vehicles, 30 days from the date of the inter-regional fiscal certificate, for motorized vehicles moved from outside the region (incoming mutation). This was done with the aim of helping to secure Regional Original Income (PAD) in North Sumatra Province, especially in the Medan City area. The most frequently encountered obstacle faced by the Medan City UPPT SAMSAT Office in collecting motor vehicle tax is the lack of public awareness in paying taxes. Public awareness is what is most needed in the implementation of motor vehicle tax payments, currently there are still many people who are reluctant or even do not immediately pay their motor vehicle tax even though the due date for paying their motor vehicle tax has passed. The attitude of the public is less aware of their duties/obligations in paying Taxpayers (WP). And most people are apathetic and don't care about paying taxes at all, the Medan City SAMSAT UPPT Office minimizes the obstacles that arise in the implementation of motor vehicle tax collection by providing a Motor Vehicle Tax Notification Letter (SPKPKB) which is sent directly to the Taxpayer according to the address listed. in the STNK